(untitled) (Global Journals of Research in Engineering, 2012)
A Mobile Ad hoc Network MANET is a new networking paradigm In the development of Mobile Ad hoc networks routing is the main issue There are different security flaws and attacks on routing protocols in MANETs These attacks can affect the performance of different routing protocols Blackhole is one of these attacks The blackhole attack can affect the performance of different routing protocols During this attack a malicious node captures packets and not forwards them in the network This paper illustrates how blackhole attack can affect the performance of routing protocol AODV in Mobile Ad hoc networks by using NS-2 34 simulator